Efeito de elevadas temperaturas, resfriamento e reidratação nas propriedades de argamassas para assentamento de alvenaria estrutural - Schmidt, Raquel Petry Brondani (2023)
Bedding mortars are important components for predicting the performance of structural masonry. In fire situations, bedding mortars can be severely damaged. The effects of high temperature exposure, cooling regimes and post-fire curing length on the properties of masonry bedding mortars were investigated in multiple studies. Three factory-made mortars with nominal compressive strengths of 4 MPa, 12 MPa and 20 MPa were tested. The specimens were exposed to high temperatures ranging from 100 °C to 900 °C, cooled in air, water and air followed by water immersion (air-water) regimes and post-fire cured in air for 1 day, 28 days and 91 days. The first study evaluated the influence of high temperatures on the macrostructural and microstructural properties of masonry bedding mortars produced with dolomitic aggregates. According to the results, physical properties (hard bulk density, ultrasonic pulse velocity and fundamental transverse resonance frequency) and mechanical properties (dynamic elastic modulus, flexural strength and compressive strength) were significantly affected as temperature increased. Mineralogical and thermal analyses showed expressive phase transformations due to the thermal treatment. Regarding mechanical properties, the dynamic elastic modulus was the most heat sensitive property and the compressive strength was the least one. The second study investigated the effect of cooling regimes on the physical-mechanical behavior of masonry bedding mortars exposed to high temperatures. Mortars were cooled in air, water and air-water cooling regimes. It was concluded that compressive strength, hard bulk density and moisture content were responsive to the different cooling regimes at 1 day and 28 days post-fire curing in most analyses. The lowest mortar residual compressive strength was already reached at 1 day post-fire curing in most analyses. At 1 day post-fire curing, water cooling showed the highest compressive strength loss among the three cooling regimes. At 28 days post-fire curing, air-water cooling resulted in the highest residual compressive strength and water cooling resulted in the highest compressive strength recovery in most analyses. The third study assessed the influence of post-fire air curing length on mechanical, mineralogical and thermal behavior of masonry bedding mortars exposed to high temperatures. The mortars were tested after 1 day and 91 days post-fire air curing. Results indicated that the dynamic elastic modulus and compressive strength of mortars could be partially or totally recovered by increasing the post-fire curing length from 1 day to 91 days in most analyses. Water cooling resulted in the highest recovery of dynamic elastic modulus and compressive strength, mainly after exposure to the highest temperatures. Mineralogical and thermal analyses explained the residual mechanical properties of the mortar specimens post-fire cured. Under an integrating analysis among the three studies, it was concluded that the lower the nominal compressive strength, the higher the limit exposure temperature for mortars heated, cooled in air and post-fire cured for 1 day. Residual compressive strength results were always lower than nominal values for mortars heated, cooled in water and post-fire cured for 1 day. The limit exposure temperatures increased more expressively during post-fire curing when the mortars were cooled in water.